2015
DOI: 10.1152/ajpendo.00277.2014
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of brown adipose tissue during cold exposure reveals extensive regulation of glucose metabolism

Abstract: We applied digital gene expression profiling to determine the transcriptome of brown and white adipose tissues (BAT and WAT, respectively) during cold exposure. Male C57BL/6J mice were exposed to cold for 2 or 4 days. A notable induction of genes related to glucose uptake, glycolysis, glycogen metabolism, and the pentose phosphate pathway was observed in BAT from cold-exposed animals. In addition, glycerol-3-phosphate dehydrogenase 1 expression was induced in BAT from cold-challenged mice, suggesting increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 77 publications
11
100
1
Order By: Relevance
“…Overall, we show that cold exposure induced fat browning and activated mitochondrial function; these results are consistent with previous studies (23)(24)(25). Therefore, we also suggest that BLC shows comparable effects to cold stimulation on fat browning.…”
Section: Blc Enhances Mitochondrial Function and Mitochondrial Biogensupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, we show that cold exposure induced fat browning and activated mitochondrial function; these results are consistent with previous studies (23)(24)(25). Therefore, we also suggest that BLC shows comparable effects to cold stimulation on fat browning.…”
Section: Blc Enhances Mitochondrial Function and Mitochondrial Biogensupporting
confidence: 93%
“…4D). Previous studies have shown that activated mitochondrial function can be induced by cold stress or b-adrenergic stimuli as well as by the expression of brown adipocyte-specific genes (23)(24)(25). Exposure of mice to cold temperatures in this study resulted in an ;15-fold increase in UCP1 mRNA levels and a significant increase in UCP1 protein levels in the scWAT of mice compared with mice at room temperature ( Supplementary Fig.…”
Section: Blc Enhances Mitochondrial Function and Mitochondrial Biogenmentioning
confidence: 53%
“…Allelic variants causing loss-of-function put human individuals at risk to develop obesity14. A comparison of our RNA-seq data with two microarray-based data sets78 and a digital gene expression profiling15 revealed that GPR120 was consistently and strongly upregulated in BAT following cold exposure. Here we set out to assess the regulation and function of GPR120 in relation to BAT activation.…”
Section: Resultsmentioning
confidence: 91%
“…It was recently shown that cold increases the expression of genes related to PPP in BAT72, a metabolic pathway required to sustain de novo lipogenesis and nucleotide biosynthesis. Here, we confirmed these findings in control mice.…”
Section: Discussionmentioning
confidence: 99%